Canine parvovirus (CPV-2) variants circulating in Nigerian dogs - Apaa, Ternenge; Daly, Janet M.; Tarlinton, Rachael E. (BMJ Publishing Group, 2016)
Canine parvovirus type 2 (CPV-2) is a highly contagious viral disease with three variants (CPV-2a, CPV-2b and CPV-2c) currently circulating in dogs worldwide. The main aim of this study was to determine the prevalent CPV-2 variant in faecal samples from 53 dogs presenting with acute gastroenteritis suspected to be and consistent with CPV-2 to Nigerian Veterinary Clinics in 2013-2014. Seventy-five per cent of these dogs tested positive for CPV-2 in a commercial antigen test and/or by PCR. Partial sequencing of the VP2 gene of six of these demonstrated them to be CPV-2a. Most of the dogs (60 per cent) were vaccinated, with 74 per cent of them puppies less than six months old.